Case Report: Novel Biallelic Variants in DNAJC21 Causing an Inherited Bone Marrow Failure Spectrum Phenotype: An Odyssey to Diagnosis - Chirita-Emandi, Adela; Petrescu, Carmen-Angela-Maria; Zimbru, Cristian G.; Stoica, Florina; Marian, Catalin; Ciubotaru, Andreea; Bataneant, Mihaela; Puiu, Maria (Frontiers in Genetics, 2022)
Bone marrow failure represents an umbrella diagnosis for several life-threatening disorders. In many people, the etiology remains unknown for a long time, leading to an odyssey to diagnosis, with numerous tests performed and sometimes inappropriate treatment. Biallelic pathogenic variants in the DNAJC21 gene were recently discovered to cause bone marrow failure syndrome type 3, having phenotypic overlap with Fanconi anemia, dyskeratosis congenita, Shwachman–Diamond syndrome, and Diamond–Blackfan anemia. Herein, we report an 8-year-old boy, with normal intellect, presenting bone marrow failure; growth retardation; failure to thrive; recurrent infections (including sepsis); cryptorchidia; skeletal, skin, teeth, and hair abnormalities; joint hypermobility; eczema; palpebral ptosis; high myopia; rod–cone retinal dystrophy; and short telomeres. He underwent several tests and evaluations, including genetic investigations (panel and exome sequencing), before the DNAJC21 gene was known to cause disease. Whole-genome sequencing performed at the age of 7 years, identified two novel, pathogenic, and compound heterozygous variants in the DNAJC21 gene: NM_001012339.3:c.148C>T (stopgain-maternal origin), p.Gln50∗ and c.643_644delinsTTT (frameshift paternal origin), and p.Lys215Phefs∗71. He received aggressive treatments for his multisystem disease: blood cell transfusions, high-dose corticosteroids, immunoglobulins, multiple antibiotics, vitamins, growth hormone, and others. However, allogeneic hematopoietic stem cell transplantation was avoided. The clinical evolution of bone marrow failure and recurrent infections stabilized with age, yet the myopia progressed. Exocrine pancreatic insufficiency was not detected. This report widens the molecular and clinical understanding of bone marrow failure syndrome type 3. Genome sequencing directed a precise diagnosis that improved patient management and enabled family genetic counseling.